Passive exercise provides a simultaneous and postexercise executive function benefit - Dalton, Connor; Edgar, Chloe; Tari, Benjamin; Heath, Matthew (Frontiers in Cognition, 2024)
Passive exercise involves limb movement via an external force and is an intervention providing an immediate postexercise executive function (EF) benefit. It is, however, unknown whether EF is improved simultaneous with passive exercise -a salient question given the advent of passive (and active) exercise workstations designed to enhance productivity and well-being for individuals engaged in sedentary occupations. Here, participants (N=23) completed separate 20min conditions involving active (i.e., via volitional muscle activation) and passive (i.e., via mechanically driven cycle ergometer) cycle ergometry and a non-exercise control condition. EF was assessed prior to (i.e., pre-intervention), simultaneous with, and immediately after (postintervention) each condition via the antipointing task. Antipointing involves a goal-directed limb movement mirror-symmetrical to a target and is an ideal tool for the current investigation given that the task is mediated via EF inhibitory control networks that show response-dependent changes following a single bout of exercise. Results showed that passive exercise produced a simultaneous and post-intervention reduction in antipointing reaction time (RT), whereas active exercise selectively produced a post-intervention -but not simultaneous -RT reduction. Thus, passive and active exercise elicited a postexercise EF benefit; however, only passive exercise produced a simultaneous benefit. That passive -but not active -exercise produced a simultaneous benefit may reflect that the intervention provides the necessary physiological or psychological changes to elicit improved EF efficiency without the associated dual-task cost(s) of volitional muscle activity.